Cosy development: sensory-motor interventions to improve verbal and expressiveness abilities for Down Syndrome children - Anik Dwi Hiremawati; Endang Rochyadi; Sunardi Sunardi; Cece Rakhmat (Universitas Udayana dan Diaspora Taipei Medical University, 2025)
Background: Existing interventions to improve verbal expression for children with Down Syndrome (DS) often neglect sensory and motor development. However, these abilities are essential for receiving input from the environment and responding through gestures during intervention. This study aimed to develop interventions through sensory and motor development that enhance the expressive verbal capabilities of DS children in articulating sounds, syllables, and words. Methods: This study used quantitative methods with an experimental design. Clinician-rated questionnaires measured the pre-test and post-test verbal expressive abilities of DS children who received the Cosy Development (CD) intervention for 12 months. Participants consisted of 8 DS children, ages ranged 4-15 years. This study was conducted at Tridiva Learning House, Bandung, Indonesia. Families of the DS children were trained by researchers regarding the intervention guidelines, and they performed the CD intervention on their children at home. Results: The Wilcoxon rank test showed a statistically significant improvement in verbal expressiveness among the eight DS children who received the CD intervention for 12 months, with p-values ranging from 0.016 to 0.008. Conclusion: The CD intervention, which integrated sensory and motor developments, effectively improved the verbal expressiveness of DS children. The CD intervention was practical and comfortable for DS children, making it a promising approach for improving their communication abilities.